PENGARUH LAMANYA PENUNDAAN TERHADAP PEMERIKSAAN ELEKTROLIT KALIUM - Denny Juraijin (IKesT Muhammadiyah Palembang, 2023)
Background : Electrolytes have a crucial role in the human body which can affect metabolism, so it needs to be maintained in balance. Imbalances of electrolytes in the body need to be anticipated by measuring or examining these electrolyte levels so that they can detect disease, establish a diagnosis, determine prognosis, become a guide in patient management, and monitor treatment. Errors in examination can have serious consequences that can lead to errors in treatment because they are based on inaccurate results. Sample handling is one of the causes of the inaccuracy of the results of the examination. It is not permissible to leave blood samples for checking electrolyte levels for too long. Therefore, this research is needed regarding the effect of delaying the examination of blood electrolytes, especially potassium, on the examination results. Research Objectives : To determine the effect of the long delay of the examination on Potassium electrolyte levels in samples of immediate examination, 12-hour delay, and 24-hour delay. Research Methods : This study used an experimental method using 30 blood samples from patients at AR Bunda Prabumulih hospital in January. Results : The average value of electrolyte levels on immediate examination was 4.11. Meanwhile, on examination with a delay of 12 hours, the average electrolyte level of Potassium was 4.10, and for the examination results from a delay of 24 hours, the electrolyte level of Potassium was 4.12. To prove whether there is an effect of delaying the inspection of Potassium on the examination results, a statistical test is carried out with the SPSS application. Conclusion : Based on the results of this study, it was stated that there was no effect of the length of delay on examining potassium electrolytes and blood samples with a delay of up to 24 hours could still be used to check blood electrolyte levels.